When Obligate Partners Melt Down - Nancy A. Moran (mBio, 2016)
ABSTRACT Insect hosts derive benefits from their obligate symbionts, including nutrient supplementation and the ability to colonize otherwise inhospitable niches. But long-term symbionts sometimes also limit the ecological range of their hosts; in particular, they are often more temperature sensitive than the hosts themselves. Even small increases in average temperature, comparable to those occurring under current conditions of climate change, can kill symbionts and, with them, their hosts. In some cases, limitations imposed by obligate symbionts may help to counter the spread of invasive pests, but they also contribute to contractions in populations and geographic ranges of invertebrate species.